Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Sistem Informasi Akuntansi pada UMKM di Pontianak - Antonius Antonius; Risal Risal; Ali Afif; Rizki Fakhrul Yahya (Program Studi Akuntansi Universitas Panca Bhakti, 2026)
The Indonesian government pays special attention to the better and more organized development of Micro, Small and Medium Enterprises (MSMEs). This is due to the rapid development and growth of MSMEs in Indonesia and the important role of MSMEs in Indonesia's economic development. MSMEs are willing to use accounting information if they feel that there are benefits or uses and convenience in using the accounting information contained in financial statements and feel a direct impact on the progress of their business (Albab et al., 2023). This study aims to determine the effect of education level, business scale, and social factors on the interest in using AIS among MSMEs in Pontianak. The population in this study was 27,183 MSMEs in the city of Pontianak. The research sample consisted of 100 MSMEs in the city of Pontianak using simple random sampling. The data collection technique used a questionnaire. Data processing and analysis were performed using multiple linear regression analysis. The results showed that, partially, education level had a positive effect on the interest in using ISA among MSMEs in Pontianak. Meanwhile, business scale and social factors had no effect on the interest in using ISA among MSMEs in Pontianak.